2020
DOI: 10.4081/jphr.2020.1794
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the Covid-19 Pandemic: The Bangladesh Perspective

Abstract: An outbreak of a COVID-19 pandemic disease, caused by a novel coronavirus SARS-CoV-2, has posed a serious threat to global human health. Bangladesh has also come under the attack of this viral disease. Here, we aimed to describe the responses of Bangladesh to tackle the COVID-19, particularly on how Bangladesh is dealing with this novel viral disease with its limited resources. The first case of a COVID-19 patient was detected in Bangladesh on March 8, 2020. Since then, a total of 263,503 peoples are officiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
154
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(158 citation statements)
references
References 13 publications
3
154
1
Order By: Relevance
“…While all age ranges are at risk of contracting COVID-19, older individuals are at significant risk of experiencing serious illness as a result of physiological changes arising from aging and possible underlying health conditions [ 19 ]. Bangladesh has a median age of 27.6 years, and the young and middle-aged in Bangladesh come mostly under the working class and are more likely to be forced to leave home for jobs and thus have a higher risk of being infected [ 20 ]. Our findings are also consistent with early reports 21 , 22 resulting that younger people are less likely to be affected, supported by several studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While all age ranges are at risk of contracting COVID-19, older individuals are at significant risk of experiencing serious illness as a result of physiological changes arising from aging and possible underlying health conditions [ 19 ]. Bangladesh has a median age of 27.6 years, and the young and middle-aged in Bangladesh come mostly under the working class and are more likely to be forced to leave home for jobs and thus have a higher risk of being infected [ 20 ]. Our findings are also consistent with early reports 21 , 22 resulting that younger people are less likely to be affected, supported by several studies.…”
Section: Discussionmentioning
confidence: 99%
“…After three confirmed cases of COVID-19 first diagnosed in Bangladesh, the government has placed in place protective measures to combat the spread of the deadly COVID-19 strain that has rattled the globe. As the virus is extremely infectious, quick diagnosis is the best way to isolate infected individuals 6 , 7 , 20 . COVID-19 deaths in Bangladesh, warned by the experts that in view of the growing number of death cases a visible scenario could be the tip of an iceberg [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [ 14 ] reported that the COVID-19 trend in Bangladesh showed deviation from the epidemiological model, and they identified potential factors responsible for this deviation. Overall, Bangladesh’s COVID-19 characteristic patterns reflect the following: an inadequate testing and treatment capacity, insufficient supply of personal protection equipment, poor public sanitation practices, poorly managed public health care system and services, lack of public awareness, large-scale violation of social distancing order ( Figure 1 , Figure 3, Figure A2 and Figure A3 ), a large vulnerable population (e.g., Rohingya refugees), community-level transmission, and dire economic impacts [ 15 ]. While existing research and unpublished reports highlight these important aspects of the COVID-19 outbreak in Bangladesh, knowledge is largely missing on the geographic perspectives of the transmission dynamics and intervention scenarios in the country.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is an infectious disease that was identified for the first time in Wuhan, the capital of Hubei province, China in December 2019 and then it spread rapidly throughout the world [6,7]. After almost three and a half months of the first COVID-19 patient detected in China, three coronavirus cases (including two men and one women) have been tested positive for the first time on 8 March 2020 in Dhaka, Bangladesh [8] where two of them returned from Italy and the other is a relative of one of the returnees. Their ages were between 20 and 35 years, which was ensured by the Institute of Epidemiology, Disease Control and Research (IEDCR).…”
Section: Covid-19 Outbreak In Bangladeshmentioning
confidence: 99%